"Let Us All Mutate Together": Cracking the Code in Laing's Big Bishop Roko and the Altar Gangsters. (21st October 2016) - MacDonald, Ian P.
Abstract : Both Derek Wright and Francis Ngaboh-Smart have interpreted Laing's Major Gentl and the Achimota Wars (1992) as an allegory for the emergence of the Internet. In that novel, a future Africa has been digitally erased from the Web archive, and the story follows a civil war aimed at reintegrating the continent into the global scene. Beginning from this reading, I approach Laing's next work, Big Bishop Roko and the Altar Gangsters (2006), as a formal sequel to Major Gentl, investigating the changing landscape of global digital access and its potential as a site of resistance over the decade that separates their publication. If, in Major Gentl, West Africans have been exiled from the Web, the eponymous protagonist in Roko uses networked access to interrupt neoliberal economic and social engineering underway in the global North. Through experiments in "genetic mutation"—a metaphor for cyborgian transformation from biological to networked existence—Roko hacks the evolutionary process and forces Africa's voice into the digital sphere in an attempt to remedy that technology's unequal distribution. In both novels, Laing indigenizes science fiction using a technique I refer to as jujutech— a hybrid of science fiction and African folk traditions. The resulting style identifies the ways the genre itself mutates and evolves as it escapes the gravity of its Euro-American roots. Laing's decision to publish Roko electronically further points to form following function, highlighting new avenues for the dissemination of experimental African works in underrepresented genres.